2000
DOI: 10.1046/j.1440-1746.2000.02200.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary use of an accuflex stent for unextractable common bile duct stones

Abstract: Endoscopic management has become the main therapeutic approach for the extraction of common bile duct (CBD) stones, and successful removal can be achieved in 80-90% patients using conventional balloon and basket techniques. However, if it is difficult to completely fragment a stone, or to clear the CBD, which may occur for a variety of reasons, the therapeutic problem will remain. When bile duct stones can not be removed, a viable management option is to place a biliary stent to ensure drainage. However, recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Based on previous use, it can be hypothesized that CSEMSs could have an advantage over plastic stents in improving subsequent duct clearance. [18][19][20] Our aim was to characterize the efficacy and safety of temporary placement of CSEMSs for cases of complex biliary stones.…”
mentioning
confidence: 99%
“…Based on previous use, it can be hypothesized that CSEMSs could have an advantage over plastic stents in improving subsequent duct clearance. [18][19][20] Our aim was to characterize the efficacy and safety of temporary placement of CSEMSs for cases of complex biliary stones.…”
mentioning
confidence: 99%
“…Biochemical changes which reduce stonepromoting factors after stenting may also facilitate stone dissolution [6,14]. In addition, stent placement may [15]. No evidence of stones was seen in many cases during the second ERCP performed after several months, meaning that spontaneous passage of stones from the bile duct has occurred [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Temporary use of a self-expanding metal stent for un-extractable BD stones was first reported in 2000 13. FC-SEMS have greater radial force than plastic stents; therefore, theoretically, they may be more successful in fragmenting the stone(s) and/or dilating the papilla.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Temporary use of a self-expanding metal stent for un-extractable BD stones was first reported in 2000. 13 FC-SEMS have greater radial force than plastic stents; therefore, theoretically, they may be more successful in fragmenting the stone(s) and/or dilating the papilla. However, only a limited number of studies reported complete stone extraction rates after FC-SEMS placement, which ranged between 82 and 100%.…”
Section: Introductionmentioning
confidence: 99%